Key technologies implementation of high-repetition-rate satellite laser ranging - Wang Peiyuan; Guo Tangyong; Gao Hao; Li Xin; Zhu Wei; Zou Tong; Li Shipeng (Geodesy and Geodynamics, 2013)
Satellite laser ranging (SLR) is one of the major space geodetic instruments, which has various applications in earth science. In this paper, we introduce several issues regarding the key technology implementation of high-repetition-rate SLR system. Compared with traditional technology, using kHz and 8 ps pulse width laser component, the data quantity and quality of high-repetition-rate satellite laser ranging (SLR) can be significantly improved. The characteristics of high-repetition-rate laser ranging and the key technologies are presented, including the event timer with the precision of picosecond, the generation of range gate signal, and so on. All of them are based on the Field Programmable Gate Arrays (FPGA) and tested on China mobile SLR system-TR0Sl000. Finally, the observations of satellite Beacon-C are given.